Creation of Artistic and Lexical Means in Translations of Literary Works (International Journal of Psychosocial Rehabilitation, 2020)
Interaction is actively carried out not only with the help of methodologically neutral linguistic means but also with the help of figurative, emotional-affective language units. After all, live speech is by nature full of colorful artistic-visual means, figurative linguistic units, and words and phrases expressing hysteria, which create the language of artistic monument attractiveness, expressiveness, folklore, and national character.